Relevansi Ajaran Agama dalam Aktivitas Ekonomi - Syafiq Mahmadah Hanafi; Achmad Sobirin (Jurnal Iqtisad, 2002)
This paper discusses the effect of the values and interpretations of religion on economic activity. We argue that although the religions influence the economic activities, but the interpretations on the religions prove to have more profound impact on the activities. Islam and Protestant –i.e. the interpretations on them- have different views on the nature of behavior and the institutions involved, being Islam emphasis ‘social’ nature and Protestant emphasizes ‘individual’ nature. These emphases lead to differences in economic activities and institutions involved.